Aktivitas Fisik, Konsumsi Makanan Asin dan Kejadian Hipertensi Masyarakat Pesisir Kota Medan - Putra Apriadi Siregar; Saidah Fatimah Sari Simanjuntak; Feby Harianti Ginting; Sutari Tarigan; Shafira Hanum; Fikha Syra Utami (Sarana Ilmu Indonesia (salnesia), 2020)
Physical activity and consumption of salty foods are some of the factors associated with the incidence of hypertension. People who consume a lot of salty foods and have less physical activity will be at greater risk of being affected by hypertension. This study aimed to find a physical activity, consumption of salty foods and the incidence of hypertension based on sociocultural coastal communities in Medan in 2019. This study used a cross-sectional study approach. The subjects in this study were 90 people in Belawan II Village. The instrument used was the basic health Research questionnaire. This study presents data on frequency distribution and cross-tabulation between physical activity and food consumption with hypertension. The results showed that the majority of subjects in this study had hypertension were adults (25-59 years) as many as 66 people, research subjects doing moderate physical activity as many as 67 people, consuming salty foods often (?1 time a day) as many as 40 people. Most of the subjects in this study who had hypertension rarely ate salty foods and undertook moderate physical activity (20.9%). It is expected that Belawan coastal communities will adopt a healthy lifestyle by reducing the consumption of salty foods and often doing physical activities in a day. Puskesmas staff is also expected to routinely check blood pressure levels and often give education about hypertension in the coastal communities of Medan City.